The Role of Insulin/IGF-1/PI3K/Akt/GSK3β Signaling in Parkinson's Disease Dementia - Yang, Liying; Wang, Hongyan; Liu, Lijun; Xie, Anmu (Frontiers in Neuroscience, 2018)
Dementia, a condition that frequently afflicts patients in advanced stages of Parkinson’s disease (PD), results in decreased quality of life and survival time. Nevertheless, the pathological mechanisms underlying Parkinson’s disease dementia (PDD) are not completely understood. The symptoms characteristic of PDD may be the result of functional and structural deficiencies. The present study implicates the accumulation of Lewy bodies in the cortex and limbic system as a potent trigger in the development of PDD. In addition, significant Alzheimer-type pathologies, including amyloid-β (Aβ) plaques and NFTs, are observed in almost half of PDD patients. Interestingly, links between PDD pathogenesis and the mechanisms underlying the development of insulin resistance have begun to emerge. Furthermore, previous studies have demonstrated that insulin treatment reduces amyloid plaques in Alzheimer's disease (AD), and normalizes the production and functionality of dopamine and ameliorates motor impairments in 6-OHDA-induced rat PD models. GSK3β, a downstream substrate of PI3K/Akt signaling following induction by insulin and IGF-1, exerts an influence on AD and PD physiopathology. The genetic overexpression of GSK3β in cortex and hippocampus results in signs of neurodegeneration and spatial learning deficits in in vivo models [26], whereas its inhibition results in improvements in cognitive impairment in these rodents, including AD and PD. Accordingly, insulin- or IGF-1-activated PI3K/Akt/GSK3β signaling may be involved in PDD pathogenesis, at least in the pathology of PD-type + AD-type.